ARCS LEARNING MODEL WITH SAFETY EDUCATION AS A LEARNING SOLUTION FOR THE NEW NORMAL ERA - Ahmad Lutfi; Akbar Muntoha Gufron; Dyana Wijayanti (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2023)
The purpose of writing this article is to describe and give an overview of ARCS learning model loaded with safety education in the new normal era. Using the writing method of literature review the author collects information related to learning in the new normal era, ARCS learning model and safety education from sharing sources ranging from books, journal articles and news media. ARCS is an instructional design learning model developed by Keller that focuses on motivation. Become a learning model to increase students' learning motivation. The ARCS model is very appropriate in the new normal era in the form of student protection through an educational perspective. It is hoped that with this reference educators can more optimally create a new normal era teaching plan that must apply health protocols strictly by paying attention to the psychological needs of students. This motivational model has four aspects that represent various motivational characteristics that exist in each individual, consisting of: attention, relevance, confidence and satisfaction. The safety educatin charge was initiated to provide provisions to students for the importance of protecting themselves and the environment from the current pandemic situation. Learning arcs model loaded with safety education can be carried out in various educational units while maintaining safety and health. So that learning activities take place optimally.